The Journal of Process Types in Transitivity System - Yuni Alfiana (LINGUISTICA, 2012)
This study concentrates on the analysis of process types in transitivity system, which is a very important branch of Halliday’s Systemic Functional Grammar. The writer turns to this theory because of its belief that language can be considered as human representation of the world or reality. From the analysis, the writer hopes that the ones who are interested in this study can learn how language represents the world inside the human beings as well as the world around them, so that the analysis can also serve as an effective way in any kinds of text analysis. Key words: Process type; Transsitivity system